Measurement of the W-boson mass in pp collisions at s = 7 TeV with the ATLAS detector - Aaboud, M; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2018)
A measurement of the mass of the W boson is presented based on proton-proton collision data recorded in 2011 at a centre-of-mass energy of 7 TeV with the ATLAS detector at the LHC, and corresponding to 4.6 fb - 1 of integrated luminosity. The selected data sample consists of 7.8 × 10 6 candidates in the W → μ ν channel and 5.9 × 10 6 candidates in the W → e ν channel. The W-boson mass is obtained from template fits to the reconstructed distributions of the charged lepton transverse momentum and of the W boson transverse mass in the electron and muon decay channels, yielding m W = 80370 ± 7 ( stat. ) ± 11 ( exp. syst. ) ± 14 ( mod. syst. ) MeV = 80370 ± 19 MeV , where the first uncertainty is statistical, the second corresponds to the experimental systematic uncertainty, and the third to the physics-modelling systematic uncertainty. A measurement of the mass difference between the W + and W - bosons yields m W + - m W - = - 29 ± 28 MeV.